2018
DOI: 10.1109/jstars.2018.2834961
|View full text |Cite
|
Sign up to set email alerts
|

Urban Land Cover Classification With Missing Data Modalities Using Deep Convolutional Neural Networks

Abstract: Automatic urban land cover classification is a fundamental problem in remote sensing, e.g. for environmental monitoring. The problem is highly challenging, as classes generally have high inter-class and low intra-class variance. Techniques to improve urban land cover classification performance in remote sensing include fusion of data from different sensors with different data modalities. However, such techniques require all modalities to be available to the classifier in the decision-making process, i.e. at te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…In this study, two machine learning algorithms including RF and SVM were applied to crop classification. Recently, deep learning algorithms including convolutional neural network (CNN) were widely applied to remote sensing data classification [54][55][56]. Despite the promising performance of CNN, Kim et al [57] reported that the training sample size has greater effects on the accuracy of CNN than that of SVM in crop classification, indicating a need for numerous training samples for improved CNN classification performance.…”
Section: Classification Methodsmentioning
confidence: 99%
“…In this study, two machine learning algorithms including RF and SVM were applied to crop classification. Recently, deep learning algorithms including convolutional neural network (CNN) were widely applied to remote sensing data classification [54][55][56]. Despite the promising performance of CNN, Kim et al [57] reported that the training sample size has greater effects on the accuracy of CNN than that of SVM in crop classification, indicating a need for numerous training samples for improved CNN classification performance.…”
Section: Classification Methodsmentioning
confidence: 99%
“…In recent years, deep neural network has shown excellent performance in the task of remote sensing image classification and segmentation [16,[39][40][41]. Feature maps output from different layers in neural network reflect different characteristics of remote sensing images.…”
Section: Urban Functional Regions Classification Based On Remote Sensmentioning
confidence: 99%
“…Note that VHR data may not be available in all areas every year. This requires DNN able to handle missing modalities (Kampffmeyer et al, 2018). Alternatively, low-level fusion is insufficiently addressed.…”
Section: Optimal Exploitation Of Data Sourcesmentioning
confidence: 99%